The Malnutrition of Obesity: Micronutrient Deficiencies That Promote Diabetes - Via, Michael (International Scholarly Research Network, 2012)
Obesity and diabetes are increasing in prevalence worldwide. Despite excessive dietary consumption, obese individuals have high rates of micronutrient deficiencies. Deficiencies of specific vitamins and minerals that play important roles in glucose metabolism and insulin signaling pathways may contribute to the development of diabetes in the obese population. This paper reviews the current evidence supporting this hypothesis.